A Study On "Donor Influence In Giving Behaviour" In Majlis Kanser Nasional (MAKNA) - Appannah, Vemanna (2004)
Non-for -Profit Organization (NPO) is an economic institution that operates like a business which serve the public without the intent of making profit or financial gain. The study of this project paper refers to Majlis Kanser Nasional (MAKNA), a NPO dedicated to provide quality life for cancer afflicted patients. receiving funds or rather collecting funds are part of their battle to sustain themselves at the fore front of the NPO business.